Cosmology for the Curious - Perlov, Delia; Vilenkin, Alex (Springer, 2017)
Cosmology is the study of the origin, nature and evolution of our universe. Its practitioners strive to describe cosmic history in quantitative detail, using the language of modern physics and abstract mathematics. Yet, at its core, our cosmological knowledge is the answer to a few fundamental questions. Have you ever drifted off deep into thought, wondering: Is the universe finite or infinite? Has it existed forever? If not, when and how did it come into being? Will it ever end? How do we humans fit into the grand scheme of things? All ancient and modern cultures have developed creation stories where at least some of these questions have been addressed. In one of the Chinese creation myths, the universe begins as a black egg containing a sleeping giant, named Pan Gu. He slept for 18,000 years and grew while he slept. Then he woke up and cracked the egg open with an ax. The light part of the egg floated up to form the sky, while the heavy part stayed down and formed the Earth. Pan Gu remained in the middle and continued to grow, pushing the sky and the Earth further apart. When Pan Gu died, his breath became the wind, his eyes the Sun and the Moon, his sweat turned into rain, and the fleas in his hair transmuted into humans.